Singing nuns and lay sisters in the Frisian houses of the Teutonic Order to 1510 - Mol, Johannes Adriaan (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
Although the Teutonic Order is not known for its interest in accommodating religious women, it did provide some space for sisters to live a godly life among the brethren. Some houses with largely male occupancy had servant half-sisters. Elsewhere, sorores are encountered as sponsors who did not perform manual labour. Furthermore, in a few places, semi-autonomous convents functioned in which nuns devoted themselves to choir prayer. However, the picture of the ways in which women were given a place is still relatively diffuse. To add depth to this, this article focuses on the situation in the Frisian circle of Order houses in the north-west of the Empire. At the Order’s two main (priest-) commanderies Nes and Schoten, sisters appear to have been attached in different forms of membership. The most recognisable is found at Schoten, which long functioned as a hospitale pauperum, where a small number of serving half-sisters were active until 1491. A second form is found at Nes, which in or shortly after 1281 founded a sub-convent for women whose task it was to provide choral prayers. Because of its narrow economic subsistence base, the community were brought back to Nes around 1375, only for it to die out there. In 1491, however, on the site of the former convent, called Steenkerk, a new convent was founded by the brothers of Nes and Schoten. This time, the occupants were lay sisters, referred to as beguines, who contributed to the economic existence of their house through manual labour. They would only wear the habit of the Teutonic Order for a short time, until 1510. This article shows that the models used for the design of the nunnery convent and the later lay sister house at Steenkerk were derived from the organisation of women’s convents of other orders in the area. For the period 1281–1375, this model was based on the Frisian double monasteries of the Benedictines and Premonstratensians, and for the period 1491‒1510, it was based on the development of lay sisters convents from the sphere of the Modern Devotion.